The Effectiveness of the Transition from Physical to Electronic Certificates - Shinta Andriyani; Arief Rahman Arief Rahman; Wiwiek Wahyuningsih Wiwiek Wahyuningsih; Mohammad Irfan Mohammad Irfan (Universitas Mataram, 2026)
Digital transformation in the land sector is part of the agenda for bureaucratic reform and the modernization of public services in Indonesia. One aspect of this transformation is the implementation of electronic land certificates developed by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). This policy was initially regulated by ATR/BPN Ministerial Regulation No. 1 of 2021 on Electronic Certificates, which was subsequently refined through ATR/BPN Ministerial Regulation No. 3 of 2023 on the Issuance of Electronic Documents in Land Registration Activities. This study aims to analyze the effectiveness of the transition from physical land certificates to electronic certificates in ensuring legal certainty regarding land rights in Indonesia. The research method used is normative legal research employing a legislative approach, a conceptual approach, and an analytical approach. The results of the study indicate that the implementation of electronic certificates provides benefits in the form of enhanced document security, service efficiency, transparency in land administration, and a reduction in the risk of certificate forgery. However, the effectiveness of this implementation still faces various obstacles, including limited digital infrastructure, low levels of technological literacy among the public, cybersecurity concerns, and the uneven validation of land data across various regions. Therefore, it is necessary to strengthen regulations, improve data security systems, accelerate the validation of land data, and enhance public outreach so that the goals of legal certainty and the protection of land rights can be optimally achieved.